Deceit and facial expression in children: the enabling role of the “poker face” child and the dependent personality of the detector - Gadea, Marien; Aliño, Marta; Espert, Raúl; Salvador, Alicia (Frontiers in Psychology, 2015)
This study presents the relation between the facial expression of a group of children when they told a lie and the accuracy in detecting the lie by a sample of adults. To evaluate the intensity and type of emotional content of the children’s faces, we applied an automated method capable of analysing the facial information from the video recordings (FaceReader 5.0 software). The program classified videos as showing a neutral facial expression or an emotional one. There was a significant higher mean of hits for the emotional than for the neutral videos, and a significant negative correlation between the intensity of the neutral expression and the number of hits from the judges. The lies expressed with emotional facial expression were more easily recognized by adults than the lies expressed with a “poker face”; thus, the less expressive was the child the harder was to guess. The accuracy of the lie detectors was then correlated with their subclinical traits of personality disorders, to find that participants scoring higher in the dependent personality were significantly better lie detectors. A non-significant tendency for women to discriminate better was also found, whereas men tending to be more suspicious than women when judging the children’s veracity. This study is the first to automatically decoding the facial information of the liar child and relating the results with personality characteristics of the lie detectors in the context of deceptive behavior research. Implications for forensic psychology were suggested: to explore whether the induction of an emotion in a child during an interview could be useful to evaluate the testimony during legal trials.